2012
DOI: 10.1016/j.ydbio.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mos/MEK/ERK cascade and Cdk1 in Ca2+ oscillations in fertilized ascidian eggs

Abstract: Intracellular calcium ion concentration ([Ca(2+)](i)) transients are observed in the fertilized eggs of all species investigated so far, and are critical for initiating several events related to egg activation and cell cycle control. Here, we investigated the role of the Mos/MEK/ERK cascade and Cdk1 on Ca(2+) oscillations in fertilized ascidian eggs. The egg of the ascidian Phallusia nigra shows [Ca(2+)](i) oscillations after fertilization: Ca(2+) waves immediately following fertilization (phase I), and [Ca(2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
(67 reference statements)
2
8
0
Order By: Relevance
“…The phosphorylation status of the MEK/MAPK pathway is one of the indicators of egg meiotic arrest and its resumption occurs following egg activation. Our present results indicated that the resumption of meiosis was linked to the MEK/MAPK pathway in A. stephensi, similar to other organisms examined so far (Tachibana et al, 2000;Kondoh et al, 2006;Sensui et al, 2012). In most vertebrates, MEK and MAPK are phosphorylated by the presence of Mos -a key component of cytostatic factor -in mature oocytes, and meiosis is arrested at meiotic metaphase II before fertilization.…”
Section: Discussionsupporting
confidence: 87%
“…The phosphorylation status of the MEK/MAPK pathway is one of the indicators of egg meiotic arrest and its resumption occurs following egg activation. Our present results indicated that the resumption of meiosis was linked to the MEK/MAPK pathway in A. stephensi, similar to other organisms examined so far (Tachibana et al, 2000;Kondoh et al, 2006;Sensui et al, 2012). In most vertebrates, MEK and MAPK are phosphorylated by the presence of Mos -a key component of cytostatic factor -in mature oocytes, and meiosis is arrested at meiotic metaphase II before fertilization.…”
Section: Discussionsupporting
confidence: 87%
“…2B″). This has also been observed in a different species of ascidian (Sensui et al, 2012). In order to extend this finding, we inhibited Cdk1 activity in fertilised eggs treated with CsA and scored for pronucleus formation, an event that is dependent on the loss of the Mos/MEK/MAPK pathway in ascidians (Dumollard et al, 2011).…”
Section: Developmentsupporting
confidence: 58%
“…Mos degradation following loss of Cdk1 activity nicely demonstrates how the upstream activating kinase (Mos) is destroyed (Castro et al, 2001;Frank-Vaillant et al, 2001). We and others have also found that maintaining Cdk1 active keeps MAPK active (Sensui et al, 2012). However, our data do not explain how MAPK is dephosphorylated, and this is crucial because phosphorylated, and therefore active, MAPK mediates the effect of the Mos/MEK/MAPK cascade.…”
Section: Mapk Inactivationmentioning
confidence: 56%
See 2 more Smart Citations